Cancer of tongue-our fixed entity - Srinivas, C. V.; P. R., Julie (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Oral cancer ranks the top three of all cancers in India. This study aimed to determine etiologic factors for squamous cell carcinoma (SCC) of the tongue and its management. Methods: This longitudinal retrospective study was conducted with 30 patients of biopsy- proven SCC of tongue diagnosed in our hospital between the years of 2010-2022. Medical records, including history of abuse of alcohol, betel nuts, tobacco products and human papillomavirus (HPV) infection were recorded. The patients details including tumour size, location, node metastasis, grade, disease recurrence, other primary cancers, delay time until diagnosis, therapy course were noted. Patients were analyzed based on etiology and management undertaken. Results: Among 30 patients with SCC tongue, 25 (83.33%) were males, 5 (16.66%) were females. Smoking was significantly higher in males (20 patients), in those 5 alcoholics. Chronic mechanical trauma was observed in 5 patients. HPV infection was observed in 2 males, 3 females had betel nut chewing habit and use of smokeless tobacco. Among 30 cases alcohol abuse, smoking, chronic mechanical traumas, HPV infection and betel nut chewing appeared as significant etiologic factors of which smoking was the most common etiology (50%). Surgical excision with neck dissection followed by radiotherapy was treatment undertaken in our study patients based on SCC tongue stage. Conclusions: our study concluded that smoking is the most common etiology of SCC tongue, the definitive treatment is surgery combined with radiotherapy based on TNM staging.